Cholinergic Pathway SNPs and Postural Control in 477 Older Adults - Arnold, Carina; Schulte, Claudia; Moscovich, Mariana; Sünkel, Ulrike; Zaunbrecher, Laura; Metzger, Florian; Gasser, Thomas; Eschweiler, Gerhard W.; Hauser, Ann-Kathrin; Berg, Daniela; Maetzler, Walter (Frontiers in Aging Neuroscience, 2018)
Objective: To determine whether single nucleotide polymorphisms (SNPs) of the cholinergic system and quantitative parameters of postural control are associated in healthy older adults. This is a cross-sectional analysis from the TREND study. Methods: All participants performed a static postural control task for 30 seconds on a foam pad in semitandem stance and eyes closed. We analyzed mean power frequency, area, acceleration, jerk and velocity from a mobile sensor worn at the lower back using a validated algorithm. Genotypes of four SNPs in genes involved in the cholinergic system (SLC5A7, CHAT, BCHE, CHRNA4) were extracted from the NeuroX chip. All participants present a normal neurological examination and a Minimental state examination score > 24. Results: 477 participants were included. Mean age was 69 years, 41% were female. One SNP of the cholinergic pathway was significantly associated with a quantitative postural control parameter. The minor allele of rs6542746 in SLC5A7 was associated with lower mean power frequency (4.04 versus 4.22 Hz; p=3.91x10-4). Moreover, the following associations showed trends towards significance: minor allele of rs6542746 in SLC5A7 with higher anteroposterior acceleration (318 versus 287 mG; p=0.005), and minor allele of rs3810950 in CHAT with higher mediolateral acceleration (1.77 versus 1.65 log(mG); p=0.03) and velocity (1.83 versus 1.74 log(mm/s); p=0.019). Intraindividual occurrence of rs6542746 and rs3810950 minor alleles was dose-dependently related with lower mean power frequency (p=0.004). Conclusion: This observational study suggests an influence of SNPs of the cholinergic pathway on postural control in older adults.